2016
DOI: 10.15376/biores.11.4.9789-9802
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based Polymer from Ferulic Acid by Electropolymerization

Abstract: Electropolymerization was carried out in order to obtain a bio-based polymer by a simple procedure. Ferulic acid, a component of gramineous plants, was selected for this purpose. A thin polymer film was produced in an organic solvent medium (i.e., CH2Cl2/methanol (4:1 v/v) in the presence of 0.2 M LiClO4), whereas it was not obtained in a totally aqueous medium (0.2 M NaOH). Scanning electron microscopic analysis showed that the polymer film had a porous lamellar structure of ~10 μm thickness. Most of the carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…Similar results were observed by da Silva [ 21 ]. The results showed that under our studied conditions, the electropolymerization of FA can take place at the three pH’s media and not only at aqueous acidic, aqueous basic, or organic media as was found by da Silva and Matsushita in their respective studies [ 21 , 22 , 23 ]. Considering the biosensor uses underphysiological conditions and to avoid pH changes from the biosensing membrane synthesis to its applications, enzyme immobilization was performed under neutral pH conditions in the presence of acetate.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were observed by da Silva [ 21 ]. The results showed that under our studied conditions, the electropolymerization of FA can take place at the three pH’s media and not only at aqueous acidic, aqueous basic, or organic media as was found by da Silva and Matsushita in their respective studies [ 21 , 22 , 23 ]. Considering the biosensor uses underphysiological conditions and to avoid pH changes from the biosensing membrane synthesis to its applications, enzyme immobilization was performed under neutral pH conditions in the presence of acetate.…”
Section: Resultssupporting
confidence: 78%
“…Likewise, it has been incorporated into biocompatible materials with biomedical applications [ 20 , 21 ]. Due to FA abundance and applications, electrochemical methodologies to detect and quantify FA in real samples have been developed, with studies showing the possibilities of FA electropolymerization, which begins with the monomer oxidation and subsequent ortho-quinone/ortho-hydroquinone system formation, followed by a radical coupling reaction allowing the polymerization [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Distinctive bands at 704, 804, 896, 1167, 1450, 1605, 2919 and ~3450 cm −1 denote γ (CO), γ (CH), γ (CCO), β (CH), ν (CC), ν (CC), ν (CH) and ν (OH) vibrational modes of caffeic acid moieties 24 . The presence of o ‐quinone, carboxyl and ester moieties in PCA films are clearly evident with the growth bands at 1602, 1653 and 1710 cm −1 25 . The absence of strong bands corresponding to the presence of the CC moiety ( γ (CH) CC , β (CH) CC and ν (CH) CC ) at 962, 1212 and 2988 cm −1 in the PCA films is indicative of the consumption of this functionality by the polymerization reaction 26 .…”
Section: Resultsmentioning
confidence: 94%
“…24 The presence of oquinone, carboxyl and ester moieties in PCA films are clearly evident with the growth bands at 1602, 1653 and 1710 cm À1 . 25 The absence of strong bands corresponding to the presence of the C C moiety (γ(C H) C C , β(C H) C C and ν(C H) C C ) at 962, 1212 and 2988 cm À1 in the PCA films is indicative of the consumption of this functionality by the polymerization reaction. 26 This fact is supported by the appearance of new bands for the C C moiety at 1035 and 1504 cm À1 .…”
Section: Characterization Of the Polymer Filmsmentioning
confidence: 99%
“…Representación de un registro voltamperométrico durante el proceso de electropolimerización de un compuesto fenólico sobre Pt. Modificado de Matsushita et al[100].…”
unclassified